The Evolution of Money Laundering Enforcement in the Cryptocurrency Age - Kadek Januarsa Adi Sudharma; Anak Agung Alit Satya Prananda, S.H. (Faculty of Law, Universitas Pekalongan, 2025)
This research examines the regulations and law enforcement efforts concerning the use of cryptocurrency as a money laundering tool in both Indonesia and the United States. Using normative legal research methods and a comparative approach, the study compares the legal frameworks of the two countries. In the United States, agencies such as FinCEN, IRS, and SEC play a critical role in enforcing laws against the use of cryptocurrencies for money laundering, with comprehensive laws and sophisticated enforcement mechanisms. Meanwhile, Indonesia relies on BAPPEBTI to oversee and regulate cryptocurrency activities. Although Indonesia’s legal framework may not be as extensive as the United States', the country has taken significant steps, such as adopting the